1963
DOI: 10.1172/jci104770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bile Salts on Glucose Metabolism by Slices of Hamster Small Intestine*

Abstract: Bile salts are known to be essential for the effective absorption of fat from the intestinal tract (1). They have been shown to stimulate the action of pancreatic lipase (2) and have an important emulsifying action on water-insoluble dietary triglycerides that is probably related to their ability to form micelles with fatty acids and monoglycerides (3). In addition to their role in triglyceride absorption, bile salts also appear to be essential in the absorption and esterification of vitamin A (4) and choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…They confirm experiments in intact rats and in rat and hamster intestinal slice preparations (8,19) that also showed glycerol incorporation into chyle or mucosal lipids. Although less than 20%c of the lipid-glycerol excreted in the urine in 24 hours was labeled, in fractional urine collections as much as 60 and 41% were incorporated.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…They confirm experiments in intact rats and in rat and hamster intestinal slice preparations (8,19) that also showed glycerol incorporation into chyle or mucosal lipids. Although less than 20%c of the lipid-glycerol excreted in the urine in 24 hours was labeled, in fractional urine collections as much as 60 and 41% were incorporated.…”
Section: Methodssupporting
confidence: 82%
“…The counting solutions used for the lipid and water soluble fractions were prepared as described previously (19). Internal standards were used in all quenched samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the pyrogenic activity of lithocholic acid in man is abolished by conjugation of the steroid with taurine but not with glycine (3). Isselbacher and his co-workers have described differences between the effects of taurine-and glycine-conjugated bile salts on glucose and fat metabolism in the small intestinal mucosa (30,31). Other substances, such as sulfate (26) and ornithine (32), which may be found conjugated with bile acids, might also therefore be expected to affect their physiological or pathological properties.…”
Section: Discussionmentioning
confidence: 99%
“…Hyamine solutions were counted with internal standards in 12 ml of toluene a scintillator (19). All other samples were counted in 15 ml of Bray's solution (20) $ Assume portal blood flow 600 ml/hr, hematocrit 40%.…”
Section: Estimation Of Medium-and Long-chain Fatty Acids-14c In Intesmentioning
confidence: 99%